The Implementation of Cooperative Integrated Reading and Composition (CIRC) Model Through Mind Mapping Method to Improve Students’ Participation in Social Studies Teaching - Melati, Harum Bunga (International Journal Pedagogy of Social Studies, 2018)
Students' learning participation in learning social science. This issue is caused by the lack of students' enthusiasm in reading and writing, in exploring the resources, and in collecting teh assignments on time, in in group activities, listening to the lectures, and in in responding question. Based on the problems, this study attempts to conduct a research on a model and method that can increase the students' learning participation. This study conducted the model of Classroom Action Study by Kemmis and Taggart with three cycles. This study used some steps of research which were namely observation, interview, and documentation for collecting the data. The subjects of this research were the 32 students of VII B SMPN 12 Bandung taken in Social Science class. This study found that CIRC model with mind mapping method shows some improvements in the students learning participation in Social Science teaching activity. The finding shows that the CIRC model with mind mapping method is effective to make the students be more active on studying the Social Science at the class.